Potato residues as an aid to aluminum sulfate in water clarification (UNED Research Journal, 2022)
Introduction: Aluminum sulfate, or iron salts, are used as coagulantsto eliminate suspended particles that produce turbidity in water for human consumption, but the process can be improved with other componets. Objective: To evaluate the use of potato peels as an aid to aluminum sulfate in water clarification. Methodology: We worked with a simulated sample of 40 UNT at 16°C with a pH of 7,16, and the CEPIS method to determine the optimal dose (7 treatments x 9 dosages factorial arrangement). Results: Aluminum sulfate + red potato peel, at 30mg/L produced the lowest turbidity (0,85 UNT at a pH of 6,99, with a removal efficiency of 98%. Aluminum sulfate + black imilla husk (35mg/L) produced a turbidity of 0,90 UNT, pH 6,96, 98% efficiency. Conclusion: Imilla and red potato are useful as a coagulation aid for aluminum sulfate.